2019
DOI: 10.1038/s41598-019-55321-5
|View full text |Cite
|
Sign up to set email alerts
|

Slowed Movement Stopping in Parkinson’s Disease and Focal Dystonia is Improved by Standard Treatment

Abstract: Patients with Parkinson’s disease and focal dystonia have difficulty in generating and preventing movement. Reaction time (RT) and stop signal reaction time (SSRT) measure the speed to initiate and stop a movement respectively. We developed a portable device to assess RT and SSRT. This incorporated a novel analysis to measure SSRT more efficiently (optimal combination SSRT, ocSSRT). After validation ocSSRT was measured in Parkinson’s disease patients without dyskinesia (PD), cervical dystonia (CD) and writer’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…Robbins ( 2000 ) noted that in marmosets manipulations of dopamine and noradrenaline tend to produce effects on tasks predominantly engaging the dorsolateral prefrontal cortex, but manipulations of the serotonergic system tend to alter performance in tests sensitive to orbitofrontal dysfunction. Interestingly, a recent study from our group (Choudhury et al, 2019 ) showed a significant reduction in SSRT after treatment with the dopamine precursor levodopa in Parkinson’s patients, potentially supporting the contention that movement stopping is mediated by circuits involving the dorsolateral prefrontal cortex.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Robbins ( 2000 ) noted that in marmosets manipulations of dopamine and noradrenaline tend to produce effects on tasks predominantly engaging the dorsolateral prefrontal cortex, but manipulations of the serotonergic system tend to alter performance in tests sensitive to orbitofrontal dysfunction. Interestingly, a recent study from our group (Choudhury et al, 2019 ) showed a significant reduction in SSRT after treatment with the dopamine precursor levodopa in Parkinson’s patients, potentially supporting the contention that movement stopping is mediated by circuits involving the dorsolateral prefrontal cortex.…”
Section: Discussionmentioning
confidence: 69%
“…In this study, we used our recently-developed method exploiting portable equipment and an analytical approach which incorporates knowledge of the likely reliability of the response probability estimates. We have shown that this provides rapid SSRT measurements with high reproducibility (Choudhury et al, 2019 ). Regardless of any methodological differences, we can have high confidence in our results since this was a double-blind placebo-controlled trial, in which we demonstrated a significant difference between placebo and 10 mg diazepam.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations